ANA E MIA MEXERAM COMIGO...MEXERAM COM VOCÊ? - MACHADO DE MELO , MARINA; NUNES DA SILVA , DANIELE; PENTEADO NUNES , GISELE; GOMES BRAZ , JORDANA; RIBEIRO RIOS , KARINA (Salão do Conhecimento, 2021)
Relato de experiência acadêmica